Cross Sectional Comparative Relationship of Obesity with Ischemic Heart Disease and its impacts. A Clinical Study - Abdul Sadiq, Abdul Ghafoor, Fazal Ur Rehman, Naheed Akhter, Rizwana Hussain, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
Study task: This study was conducted in different CCU Departments of Baluchistan from February 2022 to June 2022 for providing health awareness to the people about obesity and its effects in cardiovascular complications. Aims and Objectives: The main purpose of this study was to find out the biological effects of obesity in cardiovascular complications in both male and female individuals. Data Collection: Total 164 individuals of age in between 40- 65 were selected for this study and divided them into two different groups. In group- A, 80 individuals were non- obese of BMI 15-25 while in Group-B, 84 individuals with BMI 30-35 were so obese as compared with individuals of group-A. A medical history Performa was used to collect history of each individual. Biochemical and Physiological analysis: BMI, systolic and diastolic blood pressure, cholesterol, triglycerides, low density lipoprotein (LDL), high density lipoprotein (HDL). Ischemic heart disease and myocardial infarction were studied in connection to the obesity rate and trends of individuals. BMI calculated by dividing weight in Kg by height in m2. Automatic Digital Blood Pressure Monitor was used for measurement of systolic and diastolic blood pressure. Lipid profile was performed with the help of kits on spectrophotometer. Bio-statistical analysis: Collected raw data were presented with the application of SPSS variant 20. All findings were represented in regression of each biomarker in the form of mean standard deviation and significant changes such as (P<0.05). Results: Current study stated that an increase in ischemic heart disease in 60 (73.1%) cases of group I, and in 11 (12.2%) instances of group II. Myocardial infarction rates were also higher in obese patient substantially outperformed non-obese instances with a p value. <0.05. Additionally, obese individuals’ systolic and diastolic blood pressure levels were greater. While cholesterol, LDL, triglycerides were shown to be greater in obese people, HDL was found to be lower in these patients. Conclusion: It was concluded that obesity and weight gain are important risk factors for myocardial infarction and ischemic heart disease, which lead to poor outcomes for patients and an increase in the death rate.